(untitled) (Indian Journal of Chemistry (IJC), 2025)
Breast cancer and prostate cancer are the most common malignancy in women and men respectively. In view of serious side effects of the available therapies, cost of the treatment and drug-resistance, the search for more effective anticancer drug is urgently needed. Triterpenoids present in edible rhizomes of Nelumbo nucifera Gaetrn possess antiproliferative activities. To investigate the therapeutic effect of N. nucifera triterpenoids against breast and prostate cancers, the semi-synthetic derivatives of triterpenoids were prepared and monitored for their in vitro bioassay, molecular docking, QSAR and ADMET studies. Compound 2α,3β,24-triacetoxy hyptatic acid-A (3c) showed significant inhibitory activity against breast cancer (MCF-7, IC50 = 9.77 ± 0.9 μM) along with the strong binding affinity towards the active site of 3ERT with docking score of -7.2 kcal/mol. The QSAR model suggests the importance of geometrical shape and dipole moment of triterpenoids for their antiproliferative activity against MCF-7 cells, while AlogP and DPSA_1 is crucial for showing the activity against PC-3 cells. The ADMET analysis demonstrated that the triterpenoids follow most of the physicochemical properties required for their optimum bioavailability and not showing any toxicity. In this study, hyptatic acid-A emerged as a good structural template to develop novel leads against different cancers and substitution at C24 hydroxyl group has important role in bioactivity.